Impact of chemical reaction on thermal magnetized hybrid nanofluid over a curved stretching surface - Y. Khan; M. Nazim Tufail; Khurram Shahzad; A. Alameer; Naveed Iqbal (Results in Engineering)
This study investigated the combined effects of thermal radiation and a first-order chemical reaction on the magnetohydrodynamic (MHD) flow of a hybrid nanofluid through a porous medium. This work explores a novel model, focusing on the significant effects of thermal radiation, chemical reactions, and combined heat and mass transfer. The model also incorporates the influence of a permeable, curved, and stretching surface at the boundary, contributing to its innovative nature. The research aims to understand how these factors collectively impact the system's behavior. The hybrid nanofluid, composed of Copper and Gold nanoparticles dispersed in blood, flows over a permeable, stretchable curved surface. The governing equations along with the surface's geometric characteristics, form a system of non-linear partial differential equations (PDEs). Similarity transformations were employed to convert these PDEs into a set of ordinary differential equations (ODEs). The resulting non-linear ODEs were then solved numerically using Mathematica’s NDSolve function. The influence of various parameters on the momentum, thermal, and concentration boundary layers was analyzed through graphical representations and numerical evaluations of the surface's skin friction coefficient, Nusselt number, and Sherwood number for each dimensionless parameter. The analysis revealed that an increase in the magnetic field parameter (0.5<M<2.0) resulted in a decrease in fluid velocity, while an augmented Darcy number (0.1<K<0.7) enhanced the velocity profile. The thermal profile exhibited a diminishing trend for heat absorption (−1.0<Q<−0.1) and an increasing trend for heat generation (0.1<Q<2.6), with a decrease in temperature observed for increasing Darcy numbers (0.1<K<0.7) and an increase in temperature with increasing radiation parameter (0.1<Rd<2.0). Concentration intensified with an amplified magnetic field parameter (0.1<M<3.4)but decreased with an escalation in the chemical reaction parameter (0.1<γ<0.9) and was suppressed by the Darcy number (0.1<K<2.0).